Erratum to Agile requirements engineering practices and challenges: An empirical study [Information Systems Journal 20 (2010) 449-480] - Ramesh, B.; Cao, L.; Baskerville, Richard (Wiley-Blackwell Scientific Publications Ltd., 2015)
Erratum to Ramesh, B., Cao, L., and Baskerville, R. (2010) Agile requirements engineering practices and challenges: an empirical study. Information Systems Journal, 20, 449–480.